2022
DOI: 10.3390/s22197432
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Peripheral Artery Disease Identification Using Laboratory-Based Gait Data

Abstract: Peripheral artery disease (PAD) manifests from atherosclerosis, which limits blood flow to the legs and causes changes in muscle structure and function, and in gait performance. PAD is underdiagnosed, which delays treatment and worsens clinical outcomes. To overcome this challenge, the purpose of this study is to develop machine learning (ML) models that distinguish individuals with and without PAD. This is the first step to using ML to identify those with PAD risk early. We built ML models based on previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Al-Ramini and colleagues (2022) used gait measurements obtained by a camera system to diagnose PAD and obtained a similar accuracy of 87%. 26 Some of these gait measurements could also be used to quantify treatment effectiveness. 27 More recently, others have shown that a wearable accelerometer to estimate gait can provide similarly accurate measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Ramini and colleagues (2022) used gait measurements obtained by a camera system to diagnose PAD and obtained a similar accuracy of 87%. 26 Some of these gait measurements could also be used to quantify treatment effectiveness. 27 More recently, others have shown that a wearable accelerometer to estimate gait can provide similarly accurate measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study successfully implemented a machine learning model on gait biomechanics data to identify presence of PAD. 59 Similarly, gait analysis can provide vital information to guide the selection of treatments and develop new interventions for improving the quality of life in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings represent considerable progress in developing a model for PAD detection using gait features that can be captured in real-world settings. Previous work from our group classified individuals as having or not having PAD using biomechanics laboratory gait measurements and applying standard ML classifiers [5]. The datasets included detailed measurements of joint angles, torques, powers, and ground reaction forces.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ankle-brachial index (ABI), the standard first test for PAD diagnosis, is a specialized test that is expensive, time-consuming, and only available in appropriately equipped and staffed vascular laboratories [4], [5].…”
Section: Introductionmentioning
confidence: 99%